Expression Analysis of 1-aminocyclopropane-1-carboxylic Acid Oxidase Genes in Chitosan-Coated Banana - Kana Yamamoto; Annisa Amalia; Sastia P. Putri; Eiichiro Fukusaki; Fenny M. Dwivany (Bogor Agricultural University, Indonesia, 2018)
Banana is a climacteric fruit in which ethylene plays an important role in the regulation of the ripening process. Though it is the most produced fruit in Indonesia, the current post-harvest technologies for exporting this fruit are not economically friendly. Chitosan is one of economical biopolymer for edible coating which can extend fruit shelf-life. However, little study focused on the effect of chitosan coating has been done on gene expression level. In this study, the expression levels of several 1-aminocyclopropan-1-carboxylic acid oxidase (ACO) genes, which is an enzyme to convert 1-aminocyclopropan-1-carboxylic acid to ethylene in banana were analyzed on day 0, 1, 3, 5, 7, and 9 after ethylene treatment. As a result, one gene (ID: Ma01_t11540.1) had a similar expression pattern in both control and chitosan-coated bananas while the other genes (ID: Ma03_t02700.1, Ma05_t09360.1, Ma06_t02600.1, Ma10_t01130.1) showed different expression patterns. Among these genes, two genes (ID: Ma05_t09360.1, Ma10_t01130.1) were expressed higher than the other genes and the peak was observed on day 3. It was indicated that chitosan coating might activate the ethylene biosynthesis pathway in banana while it delayed fruit ripening.